UPAYA PENANGANAN DAN PENINGKATAN KESEHATAN MENTAL - Mohammad Ilham Maulana; Zulkipli Lessy (KOLONI, 2023)
This research aims to provide efforts to improve mental health which refers to the ability to create conditions that encourage optimal physical, mental and emotional development in individuals through harmonious interactions with other people. Mental health is a fundamental element in building social relationships, maintaining productivity, balance in daily life, and balance in relationships with the environment. When people are mentally healthy, they can grow and contribute to society. This research uses a literature review study, where the research uses a literature review by reading various books, journals and other publications related to the research topic. Indonesian people's awareness of mental health problems is believed to have continued to increase in recent months. Mental disorders used to be taboo in Indonesia, so many people ignored them. However, it is true that many groups, campaigns, social media conversations and films have emerged that center on mental health. Even though we talk a lot about mental health, it is still considered a stigma for some people. There is an assumption that those with mental health problems are crazy or possessed by demons. Apart from that, many people think that people with mental health disorders lack religious knowledge and are not close to God, even though mental disorders are brain diseases.